2018
DOI: 10.1016/j.sleep.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and remaining teeth among older people

Abstract: Compared to people with 20 or more teeth, older adults with fewer than 10 teeth have higher risks for short and long sleep durations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Their findings showed higher chances of short sleep duration among individuals with less than 20 teeth. (Al-Zahrani et al, 2020;Carra et al, 2017;Koyama et al, 2018) Like the present study, Azuma et al (Azuma et al, 2019) observed that adults reporting poor chewing ability had a higher chance of poor sleep quality.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Their findings showed higher chances of short sleep duration among individuals with less than 20 teeth. (Al-Zahrani et al, 2020;Carra et al, 2017;Koyama et al, 2018) Like the present study, Azuma et al (Azuma et al, 2019) observed that adults reporting poor chewing ability had a higher chance of poor sleep quality.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies investigating this subject were conducted among adults and mostly evaluated sleep quality, as measured by the self‐reported number of sleep hours, and used the number of teeth as the oral health measure (Al‐Zahrani et al., 2020; Carra et al., 2017; Koyama et al., 2018). Their findings showed higher chances of short sleep duration among individuals with less than 20 teeth (Al‐Zahrani et al., 2020; Carra et al., 2017; Koyama et al., 2018). Like the present study, Azuma et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long sleep duration of 9 hours or more has been shown, in several epidemiological studies to be related to an increased morbidity and mortality [32][33][34]. In addition, it was shown to be associated with a higher periodontitis prevalence among women and fewer remaining teeth among elderly [35,36]. As long sleep duration might have harmful effect, combining adequate and long sleeper into a single category would probably dilute any significant results, which would explain the inconsistency in the results between the present study and Weiner's results.…”
Section: Plos Onementioning
confidence: 99%
“…Some studies are available regarding the relationship between oral health and sleep. A cohort study found that older adults with <10 teeth are at higher risk for short and long sleep durations, compared with individuals with ≥20 teeth [9]. e findings of a cross-sectional study have suggested a positive association between sleep problems and gingival inflammation [10].…”
Section: Introductionmentioning
confidence: 99%